The attractiveness of a permanent (durabel) ruin. Contemporary functioning of the historical ruins of castles in Małopolska - Dettloff, Paweł (Protection of Cultural Heritage, 2018)
There have been presented examples of four historic castle ruins. These monuments have been thoroughly preserved lately. At the same time, measures have been taken to conduct their revitalization - development and adaptation to the tourist function. These objects are now eagerly visited. This proves that "permanent ruins" can be a great attraction without (necessary) restoration and full reconstruction. The basic elements of the program of adaptation of those ruins to the new function include: - conservation of the monument - an indispensable condition - possible "slight" addition, i.e. the shape of the building - delimiting tourist routes, including the introduction of stairs, porches (platforms), especially viewing platforms on towers, etc. - use of existing volumes (building interiors) for exhibition purposes, - accompanying infrastructure (cash registers, sanitary facilities). A great opportunity for these excesses is their use as a scenery of mass events combining fun and education: historical staging, shows and tournaments, etc. Such popularization of the past and cultural heritage is simultaneously a promotion of the monument. The use of historical ruins for tourism purposes is a great occasion for these monuments, however it also carries some risks. The danger here is "overloading" with additional - commercial attractions and making the monument seem rather kitschy.